Public e-learning opportunities in anesthesia on YouTube - Flinspach, Armin Niklas; Merk, Jana; Raimann, Florian Jürgen; Ippolito, Angelo; Vo, Linda; Blum, Lea Valeska; Noone, Stephanie; Flinspach, Mairen Heumine; Sterz, Jasmina; Neef, Vanessa (Frontiers in Medicine, 2024)
Background The increasing knowledge in medicine makes continuous education for clinicians necessary more than ever. The range of skills to be covered in anesthesia is constantly growing. How to optimize complex training in practical skills in an increasingly economized environment remains unclear. The extent and suitability to which video platforms assist in learning basic skills in anesthesia has not been investigated yet. Methods To identify appropriate videos on YouTube, we conducted a search (May 1st 2023), including common combinations of synonymous terms, and checked up to the 50th result for relevance. Videos initially deemed suitable were archived and evaluated to exclude duplicates. All included videos were subsequently scrutinized for content. For this purpose, a validated checklist to assess procedural and didactic content was used. Data analysis involved assessing interrater reliability, Spearman’s rho test, and linear regression analysis. Results We were able to include 222 videos related to 16 basic skills. The low number of videos found on specific skills was striking. The level of fulfillment illustrating a practical skill was repeatedly found <60%. The consistency of the questionnaire was moderate (Fleiss kappa 0.59). Video runtime displayed a significant correlation (p < 0.001) with the number of items accomplished on procedural (|ρ| = 0.442, R2 = 0.196) and didactic items (|ρ| = 0.452, R2 = 0.153). The professional context of the content creators showed no influence. Conclusion The quantity of available material on specific basic anesthesiologic skills varied drastically. In addition, the videos available often revealed significant shortcomings, making it challenging to easily assess the quality of the content. The vast majority of evaluated videos did not reflect the intended approach in a scientifically correct manner or were entirely unsuitable for displaying the procedural requirements.